Pengaruh CAR, NPL, LDR, NIM Dan BOPO Terhadap ROA Pada Industri Perbankan Yang Masuk Dalam LQ-45 Periode Agustus 2015 – Januari 2018 - siwu, Natalia Gabriela (JURNAL RISET BISNIS DAN MANAJEMEN, 2018)
The type of this research is associative which aims to know the influence of CAR, NPL, LDR, NIM and BOPO to ROA in banking industry which entered in LQ-45 period August 2015 - January 2018. The selected research object is banking industry included in LQ-45 August period 2015 - January 2018. Population amounted to 6 banks entered in LQ-45 during the period August 2015 - January 2018. Sampling technique used is purposive sampling. Data analysis techniques used are multiple linear analysis with the help of software program SPSS version 21. for Windows. The result showed that partially CAR and NIM have positive but not significant effect to ROA and NPL, LDR and BOPO have negative and not significant effect to ROA. From result of regression analysis also known that together independent variable that is CAR, NPL, LDR, NIM and BOPO have significant effect to dependent variable, that is ROA.Keywords: CAR, NPL, LDR, NIM , BOPO, ROA